Koenimbin induces apoptosis in MCF7 breast cancer cells with antiproliferation effect on MCF7-derived cancer stem cell (CD44+/CD24-/low) in vitro / Fatemeh Ahmadipour - Fatemeh, Ahmadipour (2018)
Apoptosis is a fundamental cellular process in the pathogenesis of cancer, and other human diseases including neurodegeneration, diabetes and coronary disease. The origin of cancer is initiated through deregulated cellular proliferation and the inhibition of apoptotic signaling processes. Breast cancer is one the most common form of malignancy in women across the world. Breast cancer stem cells (BCSCs) involve a subpopulation of tumoral cells, expressing the stem cell-associated surface markers that have a high capacity to form tumor in vivo. Inhibition of breast cancer stem cells (CSCs) revealed effective and therapeutic strategies for cancer prevention. Here, we evaluated the efficacy of Koenimbin(K), isolated from Murraya koenigii(L) Spreng, to inhibit proliferation of MCF7 breast cancer cells and target MCF7 breast cancer stem cells (CSCs) through apoptosis in vitro. Cell viability of Koenimbin-induced MCF7 was evaluated using MTT assay. Nuclear condensation, cell permeability, mitochondrial membrane potential (MMP) and cytochrome c release were observed using high content screening (HCS). Cell cycle arrest was examined using flow cytometry, while human apoptosis proteome profiler assays investigated the mechanism of apoptosis. Protein expression levels of Bax, Bcl2, and HSP70 were confirmed using Western blotting. The Caspase-7, -8 and -9 levels were measured, and the NF-κB activity was assessed using high content screening (HCS) assay. Aldefluor and mammosphere formation assays were respectively used to evaluate the inhibition effect of Koenimbin on number and size of mammospheres and enzymatic ALDH activity inMCF7 breast CSCs in vitro. It was found that Koenimbin-induced apoptosis in MCF7 cells was is mediated by cell death-transducing signals regulating MMP through down-regulating Bcl2 and up-regulating Bax, due to cytochrome c release from the mitochondria to the cytosol. Koenimbin significantly (p<0.05) induced sub-G0 iv phase arrest in breast cancer cells. Cytochrome c release triggered caspase-9 activation, which then activated caspase-7, leading to apoptotic changes. This form of apoptosis is closely associated with the intrinsic pathway and inhibition of NF-κB translocation from the cytoplasm to the nucleus. Koenimbin significantly (p<0.05) decreased the aldehyde dehydrogenase–positive cell population in MCF7 CSCs and significantly (p<0.01) decreased the size and number of MCF7 CSCs in primary, secondary and tertiary mammospheres in vitro. Koenimbin has potential for future chemoprevention studies, which may lead to the discovery of more cancer management strategies by reducing cancer resistance and recurrence and improving patient survival for clinical evaluation.